Thomas Joshua Cooper the world's edge : the atlas of emptiness and extremity - Cooper, Thomas Joshua 1946-; Govan, Michael 1963-; Morse, Rebecca ca. 20./21.Jh (Los Angeles County Museum of Art, 2019)
This book showcases Thomas Joshua Cooper’s monumental forty-five year career as a landscape photographer. Working solely with an 1898 Agfa field camera, Thomas Joshua Cooper has established himself as one of the foremost photographers of our time. His magnificent black-and-white seascapes explore specific points on the globe—often at the most remote areas, where sea and land meet. Fans of Cooper’s Atlas project, in which he has charted the Atlantic Basin, will be thrilled to find a generous selection of those images here—abstractions ranging from pitch black to clear white, and subtle gradations in between. Exquisitely reproduced, these photographs reveal the coastlines of the five continents that encircle the Atlantic Ocean. This volume also features images that deal with themes such as the earth’s changing environment, historical narratives, and North America’s great rivers and their sources. Enhancing this book are an essay by Michael Govan; biographies of the artist by Rebecca Morse and Anne Lyden, International Photography Curator at the National Galleries of Scotland; and a chronicle of the Atlas project by Christie Davis of the Lannan Foundation. Poems by Robinson Jeffers and Theodore Roethke round out this retrospective book of one of the most celebrated and distinctive photographers working today. --
"Published in conjunction with the exhibition 'Thomas Joshua Cooper: The World's Edge' at the Los Angeles County Museum of Art, Los Angeles, California (September 22, 2019-February 2, 2020). Exhibition itinerary National Galleries of Scotland, July 31, 2021-January 16, 2022"-- Provided by publisher
Keywords: Cooper, Thomas Joshua -- 1946-; Cooper, Thomas Joshua / 1946- / Exhibitions; Cooper, Thomas Joshua / 1946-; Marine photography / Exhibitions; Atlantic Ocean Region / Pictorial works / Exhibitions; PHOTOGRAPHY / Individual Photographers / Monographs; PHOTOGRAPHY / Subjects & Themes / Landscapes; PHOTOGRAPHY / Collections, Catalogs, Exhibitions / General; Marine photography; Atlantic Ocean Region; Exhibition catalogs; Exhibition, pictorial works; Ausstellungskatalog -- Los Angeles County Museum of Art -- 22.09.2019-02.02.2020 -- Los Angeles, Calif.; Ausstellungskatalog -- National Galleries of Scotland -- 31.07.2021-16.01.2022 -- Edinburgh; Bildband